Solve $\color{blue}{11x^2-99x+220 = 0}$ using factoring.
First we need to factor trinomial $ \color{blue}{ 11x^2-99x+220 } $ and than we use factored form to solve an equation $ \color{blue}{ 11x^2-99x+220 = 0} $.
Step 1: Simplify equation by dividing all coefficients by 11
$$ \begin{aligned} 11x^2-99x+220 &= 0 \,\,\, / \color{orangered}{ : 11 } \\[0.9 em ] x^2-9x+20 &=0 \end{aligned} $$Step 1: Identify constants $ \color{blue}{ b }$ and $\color{red}{ c }$. ( $ \color{blue}{ b }$ is a number in front of the $ x $ term and $ \color{red}{ c } $ is a constant). In our case:
$$ \color{blue}{ b = -9 } ~ \text{ and } ~ \color{red}{ c = 20 }$$Now we must discover two numbers that sum up to $ \color{blue}{ -9 } $ and multiply to $ \color{red}{ 20 } $.
Step 2: Find out pairs of numbers with a product of $\color{red}{ c = 20 }$.
PRODUCT = 20 | |
1 20 | -1 -20 |
2 10 | -2 -10 |
4 5 | -4 -5 |
Step 3: Find out which pair sums up to $\color{blue}{ b = -9 }$
PRODUCT = 20 and SUM = -9 | |
1 20 | -1 -20 |
2 10 | -2 -10 |
4 5 | -4 -5 |
Step 4: Put -4 and -5 into placeholders to get factored form.
$$ \begin{aligned} x^{2}-9x+20 & = (x + \color{orangered}{\square} )(x + \color{orangered}{\square}) \\ x^{2}-9x+20 & = (x -4)(x -5) \end{aligned} $$Step 5: Set each factor to zero and solve equations.
$$ \begin{array}{ccc} \begin{aligned} x-4 &= 0 \\ x &= 4 \end{aligned} & ~ & \begin{aligned} x-5 &= 0 \\ x &= 5 \end{aligned} \end{array} $$